Estudo de sistemas poliacrilamida / goma xantana / tensoativos como aditivos de fluido de perfuração base água - Cândido, Herick de Bulhões (2016)
The rheological behavior of drilling fluids is essential to determine the best composition and treatments to be applied to fluids. This project presents a study of the rheological behavior of Polymer - Surfactant systems for use such as viscosifying additives in the base fluid water. The additives used were polymers Xanthan Gum (GX) and polyacrylamide (PAC) and the surfactants Soap Base (anionic) and Cetremid (cationic). The systems were subjected to rheological characterization of various surfactant concentrations at fixed polymer concentration. The rheological characterization was performed using rheology testing system using coaxial cylinders, where it obtained the flow curves, viscosity curves for each system. From the generated curves were applied mathematical model best represented the systems as well as the parameters of this model. In all systems the model of Herschel-Bulkley was best represented the behavior and can classify them as Plastics (Pseudoplastic with yield strength). From the rheological characterization, it was possible to determine and use concentrations with the highest viscosity values, which were Polyacrylamide with 400 ppm soap base and polyacrylamide with 400 ppm Cetremide. From the chosen concentrations were made three (3) fluids modifying only the viscosifying additive, the Fluid A (XG), Fluid B (PAC), Fluid C (PAC + 400ppm Soap Base), and Fluid D (PAC + Cetremide 400 ppm). Then rheological test was carried out with the aid of a field viscometer with the formulated fluids. Despite the Polymer - Surfactant solutions deliver better rheological results when added to the drilling fluid with other additives of the base formulation, had a substantial fall of viscosifying potential, which can be explained by the interference of NaCl and KCl salts in the polyacrylamide hidratation. So Fluid A (XG) showed the best results rheology.